Inovasi Media Sosial dalam Mendukung Pengembangan Wisata Edukasi di Teba Majalangu Kesiman, Bali - Ade Sintya Devi; Ida Bagus Putra Yadnya; Kadek Ayu Ekasani (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The importance of educational tourism in Indonesia and Bali lies in its ability to combine education with tourism experiences, empower local communities, and support cultural and environmental preservation. With the right approach, educational tourism can become one of the main pillars in the development of sustainable tourism in Indonesia. The development of educational tourism in Indonesia and Bali not only provides educational benefits for visitors but also supports local economic growth and cultural preservation. With the proper approach, educational tourism can serve as an essential pillar in the development of sustainable and inclusive tourism. This study aims to design an innovative social media content strategy to increase the visibility of culture- and agriculture-based educational tourism at TeBA Majalangu, Kesiman, Bali. The research method used is qualitative with a case study approach, conducted through field observations, in-depth interviews, and social media content analysis. The results show that TeBA Majalangu’s social media is currently managed incidentally, lacking consistency in posting frequency and without a strong narrative structure. Based on these findings, the author developed an innovative social media model consisting of five main content categories: educational storytelling, interactive videos, visual education, user-generated content, and interactive content. As a form of implementation, prototypes were also created, including storyboard reels, educational carousel posts, interactive polls, Instagram feed mockups, and a one-month content calendar. This strategy is expected to serve as a reference for managers in strengthening TeBA Majalangu’s digital image as an educational tourism destination based on local wisdom that is relevant, inspiring, and sustainable. In today’s digital era, social media offers great opportunities to maximize the promotion of educational tourism, strengthen direct interaction with potential visitors, and disseminate information. With the right innovations in social media strategy, TeBA Majalangu is expected to increase the number of visitors and contribute more significantly to empowering local communities.